2021
DOI: 10.1002/nau.24636
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of urinary incontinence among women with diabetes in the Lolland‐Falster Health Study, Denmark

Abstract: Aims: To investigate the prevalence of urinary incontinence (UI) and UI subtypes (stress, urgency, and mixed UI) in women with or without diabetes mellitus; and to investigate the association between diabetes and UI (any and subtypes). Methods: A cross-sectional study based on the Lolland-Falster, Denmark population-based health study. From 2016 to 2020, clinical measurement, questionnaires, and blood tests were collected. A total of 8563 women aged 18 or older were enrolled. Data analysis included 7906 women.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Studies on diabetes and urinary incontinence have ranged from detecting a small 25 , 49 or nonsignificant 18 , 50 association (ORs from 1.1 to 1.3) to large associations in excess of twofold. 42 , 51 Our sample composition and model covariates were most similar to those of Ebbesen and colleagues 49 and Løwenstein and colleagues, 50 and results are remarkably consistent — an OR of 1.20 in our study, 1.21 by Ebbesen and 1.11 by Løwenstein. Our analysis suggested that this association may be driven by type 2 more than type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on diabetes and urinary incontinence have ranged from detecting a small 25 , 49 or nonsignificant 18 , 50 association (ORs from 1.1 to 1.3) to large associations in excess of twofold. 42 , 51 Our sample composition and model covariates were most similar to those of Ebbesen and colleagues 49 and Løwenstein and colleagues, 50 and results are remarkably consistent — an OR of 1.20 in our study, 1.21 by Ebbesen and 1.11 by Løwenstein. Our analysis suggested that this association may be driven by type 2 more than type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study published in 2020 that included 398 diabetic women from Taif, a city in the western province of Saudi Arabia, found that 34% of them suffer from UI ( p < 0.05) [ 41 ]. A study from Denmark found that the prevalence of UI was 50.3% in diabetic participants and 39.3% in participants without diabetes mellitus (DM) [ 42 ]. The pathophysiology of UI in diabetes is related to diabetic autonomic neuropathy in the form of overactive bladder, voiding dysfunction, and urinary retention [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women are more affected by this condition, considering pelvic anatomy, pregnancy, and climacteric conditions, among other factors. International studies indicate that the prevalence of incontinence in women is higher than 40%, and this indicator may reach 50% in the presence of diabetes mellitus [2][3][4][5] . It is estimated that more than 200 million people have some type of incontinence, of which 50% have UUI, thus confirming the magnitude of the problem 6 .…”
Section: Introductionmentioning
confidence: 99%